Low‐dose desoxycorticosterone pivalate treatment of hypoadrenocorticism in dogs: A randomized controlled clinical trial. (10th June 2021) - Vincent, Alysha M.; Okonkowski, Linda K.; Brudvig, Jean M.; Refsal, Kent R.; Berghoff, Nora; Olivier, N. Bari; Langlois, Daniel K.
Abstract: Background: Desoxycorticosterone pivalate (DOCP) is a commonly used mineralocorticoid replacement for dogs with primary hypoadrenocorticism (HA), but manufacturer‐recommended dosing protocols can be cost‐prohibitive. Recent reports also have raised concerns that label dose protocols could be excessive. Objective: To investigate the relative efficacy and adverse effects of 2 DOCP dosages in dogs with primary glucocorticoid and mineralocorticoid deficient HA. Animals: Thirty‐seven dogs, including 19 test population dogs and 18 controls. Methods: Randomized controlled double‐blinded clinical trial. Dogs with newly diagnosed primary HA were assigned to standard (2.2 mg/kg q30d, control population) or low‐dose (1.1 mg/kg q30d, test population) DOCP treatment. Clinical and laboratory variables were assessed 10 to 14 days and approximately 30 days after each DOCP treatment for 90 days. Results: Mean serum sodium to potassium ratios at reevaluations were ≥32 in both populations throughout the study. No dog developed electrolyte abnormalities warranting medical treatment, although hypokalemia occurred on at least 1 occasion in 9 controls and 6 test population dogs. Urine specific gravities (median, interquartile range) were lower in control dogs (1.022, 1.016‐1.029) as compared to test population dogs (1.033, 1.023‐1.039; P = .006). Plasma renin activity was overly suppressed on 84 of 104 (80.8%) assessments in control dogs whereas increased renin activity occurred on 23 of 112 (20.5%) assessments in test population dogs. Conclusions and Clinical Importance: Low‐dose DOCP protocols appear to be safe and effective for treatment of HA in most dogs. Standard‐dose protocols are more likely to result in biochemical evidence of overtreatment.